Exploring the interaction between depression and learning in Shona culture : a study of students and lecturers in a tertiary education institution in Zimbabwe. - Mhlanga, Songile (University of Stellenbosch, 2022)
Depression is one of the most common psychological problems encountered by students in higher and tertiary education yet remains under-researched particularly in indigenous cultures. This study explores how Shona students in a tertiary institution in the Midlands Province of Zimbabwe understand depression and how it interacts with their learning. Guided by the pragmatic paradigm, the study adopted a sequential mixed-methods approach to facilitate the collection of both qualitative and quantitative data in order to make the research comprehensive. Quantitative data were initially collected through the use of the Beck Depression Inventory II (BDI-II). The questionnaire informed the study of the prevalence and severity of depressive symptoms in a sample of 367 volunteer first-year students. Qualitative data were collected using a semi-structured interview guide from 11 volunteer students exhibiting severe symptoms of depression as informed by the BDI-II ratings. Thirteen volunteer lecturers who taught these students were also interviewed. This approach facilitated triangulation of data-collection sources and methods to provide stronger evidence for conclusions through convergence and corroboration of findings. Quantitative data were analysed using the Statistical Package for Social Sciences (SPSS) and qualitative data were thematically analysed. The study discovered a 36 per cent prevalence rate of depressive symptoms with no significant differences in prevalence rates for males and females. The findings indicate that the Shona students and lecturers understand depression largely as stress, thinking too much, “kufungisisa”, sadness, “kusuruvara”, mental instability, and as spiritually orientated. The students experience somatic, emotional and cognitive symptoms of depression stipulated in the DSM-5, as well as feelings of loneliness, anger, lack of a social life, missed menstrual cycle and “pain in the heart”. Depression inhibits optimal academic performance in the students and leads to a lack of concentration and motivation, a failure to meet academic demands, indiscipline, and alcohol, drug and substance abuse. The study recommends on-campus professional counselling services and programmes to increase mental health literacy and aid the prevention of depression.